2018
DOI: 10.1590/1980-4415v32n62a23
|View full text |Cite
|
Sign up to set email alerts
|

El Uso del Conocimiento Matemático en las Comunidades de Ingenieros. Del Objeto a la Funcionalidad Matemática

Abstract: Resumen En este artículo discutimos la falta de marcos de referencia para atender la justificación funcional matemática que demandan otros dominios de conocimiento como la ingeniería. La matemática escolar habitual es problematizada, considerando su función dual como herramienta y como objeto de estudio, desde la Construcción Social de la Matemática. En este sentido, con la Teoría Socioepistemológica de la Matemática Educativa, estudiamos el uso del conocimiento matemático que emerge de las comunidades de inge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 2 publications
0
4
0
5
Order By: Relevance
“…[18] To start with the design of the teaching experiment, the researchers inquired into types of mathematical models used by food technologists or engineers. The results allowed an approximation to the use that engineers make of mathematical models [15]. As a result, the importance of the interpretation of graphs, knowledge of food processes and engineering design were identified [19].…”
Section: Design and Implementation Of Teaching Experimentsmentioning
confidence: 98%
See 3 more Smart Citations
“…[18] To start with the design of the teaching experiment, the researchers inquired into types of mathematical models used by food technologists or engineers. The results allowed an approximation to the use that engineers make of mathematical models [15]. As a result, the importance of the interpretation of graphs, knowledge of food processes and engineering design were identified [19].…”
Section: Design and Implementation Of Teaching Experimentsmentioning
confidence: 98%
“…Some studies have shown that the teaching of mathematics is not related to the daily practices of engineers [1,15]. Therefore, it becomes necessary to study and promote educational practices that generate stronger links between mathematical procedures and mathematics as actually used by engineers [8,15]. These links should generate horizontal relationships between mathematical and engineering knowledge and practice [15].…”
Section: On the Notion Of A Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Por ello, ha llamado la atención de muchos autores (Arias-Rueda, 2018;Armas et al, 2016;Búa, Fernández, & Salinas, 2015;Costa & Río, 2019;Fabra & Deulofeu, 2000;Pino-Fan, Guzmán, Font, & Duval, 2017;Vargas, Reyes, & Cristóbal, 2017) que se han dedicado a estudiar la influencia de este concepto en otros campos dentro y fuera de la matemática, así como también a proponer estrategias didácticas que faciliten el aprendizaje y apropiación del concepto por parte de los estudiantes de manera natural. Por ejemplo, la formación de un ingeniero debe inducirle a considerar todas las representaciones técnicas y científicas como modelos matemáticos (Bueno & Pérez, 2018), pero para ello debió adquirir este hábito durante su proceso de formación (Mendoza-Higuera & Cordero, 2018).…”
Section: Dificultades En La Adquisición Del Concepto De Funciónunclassified